2021
DOI: 10.4236/acs.2021.114040
|View full text |Cite
|
Sign up to set email alerts
|

Wildfires in Botswana and Their Frequency of Occurrence

Abstract: Fires play an essential part in the maintenance of the environment, but amplified fire activity often leads to adverse effects in the environment such as destruction of property and loss of life. Botswana has experienced wildfires that are caused by humans intentionally and unintentionally. Some of these wildfires grow into mega fires such as the 2008 wildfires. Data of wildfires reported in Botswana from the Department of Forestry and Range Resources and the frequency of occurrence was studied and analyzed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…There will also be a further increase of 50 % by 2050 compared to the current fire numbers (WMO, 2022). For Botswana, Maabong and Mphale (2021) reported that the El-Niño/La-Niña oscillation in Southern Africa can lead to the growth of plants and thus an increase in fuel. That would be followed shortly by the occurrence of wildfires, which ranged from 37 to 938 between 2006 and 2017 in Botswana (Maabong and Mphale, 2021).…”
Section: Integrating Remarks On the Data Analysis And Comparison With...mentioning
confidence: 99%
See 2 more Smart Citations
“…There will also be a further increase of 50 % by 2050 compared to the current fire numbers (WMO, 2022). For Botswana, Maabong and Mphale (2021) reported that the El-Niño/La-Niña oscillation in Southern Africa can lead to the growth of plants and thus an increase in fuel. That would be followed shortly by the occurrence of wildfires, which ranged from 37 to 938 between 2006 and 2017 in Botswana (Maabong and Mphale, 2021).…”
Section: Integrating Remarks On the Data Analysis And Comparison With...mentioning
confidence: 99%
“…For Botswana, Maabong and Mphale (2021) reported that the El-Niño/La-Niña oscillation in Southern Africa can lead to the growth of plants and thus an increase in fuel. That would be followed shortly by the occurrence of wildfires, which ranged from 37 to 938 between 2006 and 2017 in Botswana (Maabong and Mphale, 2021). On a broader time scale, the number of wildfires in Botswana ranged from about 20 to about 350 between 1994 and 2009, with most of them being of human origin (Maabong and Mphale, 2021).…”
Section: Integrating Remarks On the Data Analysis And Comparison With...mentioning
confidence: 99%
See 1 more Smart Citation